Alteration of Bakken reservoir rock during CO2-based fracturing—An autoclave reaction experiment. (June 2016) - Lu, Jiemin; Nicot, Jean-Philippe; Mickler, Patrick J.; Ribeiro, Lionel H.; Darvari, Roxana
Highlights: Impact of O2 impurity on carbonate reservoir for geological CO2 storage is investigated. Two carbonate samples were reacted with brine, CO2 or CO2 –O2 mixture under reservoir condition. The addition of O2 had insignificant impact on carbonate rock. Including small O2 content in the injection gas stream could reduce capture cost. Abstract: This study was conducted to document and assess the effects of fluid–rock interactions when CO2 is used to create the fractures necessary to produce hydrocarbons from low-permeability rocks. The primary objectives are to (1) identify and understand the geochemical reactions of CO2 -based fracturing, and (2) assess potential changes in porosity and permeability of formation rock. Autoclave experiments were conducted at reservoir conditions exposing middle Bakken core fragments to CO2 -saturated synthetic formation brine and to supercritical CO2 (sc-CO2 ) only. Ion-milled core samples were examined before and after the reaction experiments using scanning electron microscopy (SEM), which enabled us to image the reaction surface in extreme detail and unambiguously identify mineral dissolution and precipitation. The most significant change in the reacted samples exposed to the CO2 -saturated brine is dissolution of the carbonate minerals, particularly calcite, which shows severe corrosion. Dolomite grains were corroded to a lesser degree. Quartz and feldspars remained intact, and some pyrite framboids underwent slight dissolution. Additionally, a small amount of calcite precipitation took place, as indicated by numerous small calcite crystals formed at the reaction surface and in the pores. The changes of aqueous chemical composition are consistent with the petrographic observations with an increase in Ca and Mg and associated minor elements, and a very slight increase in Fe and sulfate. When exposed to sc-CO2 only, changes observed include etching of the calcite grain surface and precipitation of salt crystals (halite and anhydrite) due to evaporation of residual pore water into the sc-CO2 phase. Dolomite and feldspars remained intact, and pyrite grains were slightly altered. Mercury intrusion capillary pressure (MICP) tests on reacted and unreacted samples show an increase in porosity when an aqueous phase is present but no overall porosity change with sc-CO2 . The results also show an increase in permeability for brine-reacted samples.